Ethnomedicinal Plants Used by ’Sherdukpen’ Ethnic Group of Shergaon Village, West Kameng District of Arunachal Pradesh - Thungon, Sange Dondu; Krishnambika, Natalya (Indian Forester, 2017)
This study on the ethnomedicinal use of plants cover an area inhabited by ’Sherdukpen’ community in West Kameng district of Arunachal Pradesh. The present study revealed that the ’Sherdukpen’ community has been using 23 different types of medicinal plants belonging to 21 different families for the treatment of 16 types of ailments. Among the 23 identified plant species, 46% belongs to herbs, 32% to trees, 18% to shrubs and 4% to lichen. It was also observed that the use of aerial plant part was higher (94.1%) than the underground plant part (5%). Fruits (29%) were predominantly used followed by leaves (23%) and least was recorded for rhizome and bark (6%). The highest use value was recorded for Swertia chirayita (0.64), followed by Artemisia vulgaris (0.61). The ICF (informant consensus factor) value was found to range from 0.80 to 1.00, which indicates great homogeneity among informant. The study also compared the indigenous plant use with available pharmacological report and found that use of 15 species coherent with known pharmacological properties.